Small mammal utilization by Middle Stone Age humans at Die Kelders Cave 1 and Pinnacle Point Site 5-6, Western Cape Province, South Africa. Issue 101 (December 2016) - Armstrong, Aaron
Abstract: Reported here are the results of a taphonomic analysis of the small mammals (between 0.75 kg and 4.5 kg adult body weight) and size 1 bovids (≤20 kg adult body weight) from the Middle Stone Age (MSA) sites of Die Kelders Cave 1 (DK1) and Pinnacle Point Site 5-6 (PP5-6), Western Cape Province, South Africa. This study provides a comprehensive taphonomic analysis of MSA small mammals with a focus on discerning the role of humans in their accumulation and the implications for human behavioral adaptations. Based on comparisons with control assemblages of known accumulation, it is evident that humans accumulated many of the Cape dune mole-rats, hares, and size 1 bovids at DK1. The patterning of cut-marked and burned mole-rat remains at DK1 provides evidence in the MSA for the systematic utilization of small mammals for their skins and as a protein source. Unlike DK1, small mammals and size 1 bovids constitute only a small portion of the PP5-6 mammals and they exhibit little evidence of human accumulation. Nocturnal and diurnal raptors accumulated most of the small fauna at PP5-6. The nominal presence of small mammals in the PP5-6 fauna is atypical of MSA sites in the Cape Floristic Region, where they are abundant and often constitute large portions of MSA archaeofaunas. DK1 humans maximized the environmental yield by exploiting low-quality resources, a strategy employed possibly in response to localized environmental conditions and to greater human population densities. In comparison, the MIS5-4 humans at PP5-6 did not exploit small mammals and instead focused on higher-quality resources like shellfish and large ungulates. Humans and predators accumulated few small mammals at PP5-6, suggesting that these taxa may have been less abundant near the site and/or that humans could afford to concentrate on high-quality resources, perhaps because of a higher-yield local environment. This study suggests that an adaptive response to the environmental conditions of MIS4 was to maximize the resource yield of local habitats to include lower-quality resources when necessary. The incorporation of these resources in the face of changing environmental and perhaps population pressures is a subsistence adaptation that played a crucial role in the population stability and expansion evidenced by the number of sites in the Cape dating to MIS4.